RESPON PENGEMBANGAN PERTANIAN ORGANIK TERHADAP PENDAPATAN USAHATANI PADI DI DESA BABATAN LINTANG KANAN KABUPATEN EMPAT LAWANG - Agoes Thony (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2017)
The purpose of this research is to: (1) Analyze the income and feasibility of organic rice farming developed in Babatan Village, Lintang Kanan Sub-district, Empat Lawang Regency, (2) To know the community response in the development of organic rice in Babatan Village, Lintang Kanan District, Empat Lawang District. This research was conducted in regency of Empat Lawang of South Sumatera Province. The determination of the location of the research is purposive or purposive, considering that in Desa Babatan Kecamatan Lintang Kanan, Empat Lawang regency is one of the villages that develops organic rice farming and the area has enough population in the research criteria. The data collection at the research location will be conducted in March 2015 until it is completed. The research found that average rice production yield is 1,419 kg / production with average price of organic rice Rp 10.000 / kg so that the average revenue of Rp 14,191,200 / production is obtained. Average production cost incurred Rp 6.896.820 / production and earned an average income of Rp 7,294,380 / production. Judging from the amount of revenues greater than the total total cost incurred, the production of organic and inorganic paddy rice has a positive income so that it is financially profitable. The response of farmers to the development of organic rice in Babatan Village is dominated by medium response because the community is still in the learning stage in the effort of developing organic rice in Babatan Village, Empat Lawang Regency.